Investigation of mathematical and educational values in the Bedeyé tradition within the traditional trading system of the Sasak tribal community - Fauzi, Lalu Muhammad; Hayati, Nila; Satriawan, Rody; Ali, Muhamad; Juaini, Muhamad; Yazid, Muh (Journal of Honai Math, 2024)
Indonesia boasts a rich and diverse traditional culture, shaped by its historical context, geographic conditions, religious influences, values, and the varied experiences of its people. The distinctiveness and variety of these traditional cultures offer valuable insights and serve as resources for learning mathematics and economics. Common perceptions often dissociate mathematics from everyday activities such as farming, trading, and other practical tasks. This research aims to investigate the mathematical principles embedded in the Bedeyé activities within the traditional economic and trade practices of the Sasak tribe. Employing a qualitative research approach with ethnographic methods, data were gathered through observation, literature review, and interviews with cultural practitioners, traditional traders, community leaders, and cultural experts. The research findings reveal that Bedeyé activities exemplify traditional barter-based trading practices, where goods are exchanged for other goods. The mathematical concepts identified in the Bedeyé tradition include comparative mathematics, set theory, and volume estimation. Moreover, the educational values inherent in Bedeyé activities encompass itiq, saling redaq, semaiq, and saling saduq. These mathematical principles observed in the traditional trading systems of the Sasak tribe, as demonstrated through Bedeyé activities, can be leveraged as educational tools and foundational elements for teaching mathematics.